Android Based Personal Finance Management Application: Design and Development - Brilly Andro Makalew (Bina Nusantara University, 2022)
The aim of this work is to design an application with the main function to ease the user in the process of managing their personal finance. The process of evaluating their financial activities record should becomes easier because the application enables their own financial goal to be monitored, controlled, and evaluated using the data. There are two phases in this research: (1) concept evaluation phase, and (2) content realization phase. The first phase produced a list of approved features that had undergone a series of concept testing. All features support all three time period: past, present, and future. Users can see their past activities, record their present transaction, and plan their future goals. The second phase produced a design for a mobile application, specifically in a form of use case diagram and class diagram. Feature comparison between similar applications had also been done twice, in the beginning and at the end. All process are done to ensure that the concept are designed as objective as possible.